IMPACT OF TEMPERATURE AND RAINFALL ALTERATIONS ON SPAWNING BEHAVIOUR OF INDIAN MAJOR CARPS AND CONSEQUENCE ON FISHERS’ INCOME IN ODISHA - DAS, M. K.; SRIVASTAVA, P. K.; DEY, S.; REJ, A. (Journal of the Inland Fisheries Society of India, 2021)
The present communication assessed the impact of the changes in climatic variables, viz. temperature and rainfall on the spawning of Indian Major Carps (IMC) in the river Mahanadi, in the fish hatcheries in its plains and on the fishers’ income in five districts of Odisha. The average minimum and maximum temperature throughout the state has increased in the range of 0.1 °C to 0.9 ºC. The annual rainfall in Cuttack and Puri districts have increased by 27.78 mm and 13.20 mm respectively and decreased by 18.73 mm, 16.25 mm, 7.4 mm, 86.88 mm and 11.25 mm in Angul, Balasore, Khurda, Sambalpur and Bolangir districts, respectively during 1981-2010. The fish spawn availability has decreased drastically in river Mahanadi in three decades from 30-43 ml net-1day-1 to the present level of 6 ml net-1day-1. The study revealed that the onset of the breeding period of the Indian major carps has advanced by one month in the hatcheries, compared to the previous two decades. The advancement in breeding period of IMC in the fish seed hatcheries in Balasore, Khordha, Puri and Mayurbhanj districts can be attributed primarily to the effect of increased water temperature and shifting of the rainfall pattern facilitating early maturation and spawning. The respondents in the fish seed hatcheries surveyed also perceived temperature and rainfall as the most important factors responsible for advancement of the onset of breeding of IMC. Key words : Climate change, breeding season, Indian major carps, hatchery, Mahanadi river basin, Odisha, India